ANALISIS BUKU BAHASA ARAB KELAS 10 DIREKTORAT KURIKULUM SARANA KELEMBAGAAN DAN KESISWAAN (KSKK) TINJAUAN KONTEN BERDASARKAN TEORI MACKEY - Farobi, Muhammad Al; Al Azmi, Fadilah; Hidayatullah, Achmad Dzulqornain; Daroini, Slamet (STIQ Amuntai, 2022)
of KSKK (content review based on Mackey theory) aims to determine the feasibility of textbooks based on Mackey's theory so that teaching materials can be used in learning. This article uses a qualitative approach with a library research model. As for the data collection is to use documentation and data analysis techniques using content analysis. In analyzing teaching materials, Mackey's theory provides a good overview of aspects that need to be considered in analyzing teaching materials, including 1) selection; 2) gradation; 3) presentation; 4) reps. From these four aspects, it can be concluded that the aspect of the selection of textbooks is still general, but the material's content tends to be more complex. In contrast, from the aspect of gradation, it has fulfilled the aspects of grouping and grading. As for the presentation aspect, it has fulfilled the differential, potential, pictorial, and context procedures. Meanwhile, the repetition aspect has been fulfilled in the form of various evaluations.